Perceived Stress, Work-Related Burnout, and Working From Home Before and During COVID-19: An Examination of Workers in the United States. (November 2021) - Hayes, Sherrill W.; Priestley, Jennifer L.; Moore, Brian A.; Ray, Herman E.
The purpose of the study was to understand the impact of involuntary remote working during the early phases of the COVID-19 pandemic on perceived stress and work-related burnout for workers with and without previous experience of remote work. The authors developed a questionnaire, open from March 23rd to May 19th, 2020, incorporating the Perceived Stress Scale, Copenhagen Burnout Inventory, demographic, and work-related questions. This sample consisted of 256 professionals who self-identified as working at home during the pandemic. Pandemic restrictions increased perceived stress for all participants, but age and gender had significant effects on stress and burnout. Burnout was most significant for respondents already working remotely before COVID-19. The most significant challenges reported were—communication, collaboration, and time management with colleagues via technology. Working from home may contribute to higher levels of perceived stress and work-related burnout, which questions moves by some employers to make working from home a permanent arrangement.